HITS-Brazil: Translation and adaptation for the context of domestic violence against the elderly (Research, Society and Development, 2020)
The aim of this study was to translate and cross-culturally adapt the Hurt Insult Threatened Scream (HITS) instrument to the Portuguese language for tracking domestic violence against the elderly. Therefore, it was necessary the application of strict methodological criteria in order to ensure its trustworthiness to the use by other researchers tracking information regarding violence against the elderly. The study was developed in five steps to attend all the semantic, idiomatic, experimental and conceptual requirements broadly used by other researchers. After the early stages – initial translation; synthesis of the translations; retro translation –, two versions of the scale were created, one made by a professional translator and another created by a health care professional. These versions were used on the fourth stage, which consists on the final version of the scale, that was submitted to the assessment of a specialized group with the purpose of attending to specific relevant criteria on the subject studied. Finally, on the fifth step, was realized on a pre-test with 30 elderly citizens. The data collected was analyzed using IBM Statistical Package for the Social Sciences® based on descriptive statistics. In addition to the final version, were applied an instrument to assess social-demographic characteristics and Leganés cognitive assessment. According to the evaluation of the committee two items needed to be improved, for presenting low compatibility regarding some observed equivalences. As a final result, we present the HITS-Brazil properly adapted to the Brazilian context.